Women in Information and Communication Tech (ICTs): Breaking gender barriers (Research, Society and Development, 2024)
This article analysis of the inclusion of women in the Information and Communication Technology Technology (ICT) in the city of Humaitá, Amazonas. In this context, this aims to analyze women's views on the area and to identify the causes of dropout and participation in technical training courses at the Instituto Federal do Amazonas, Humaitá campus. The research was carried out with 22 students on the IT course aimed at socially vulnerable women. Focus groups and content analysis were used to collect the data. The results, we identified that the women recognize the predominance of the male gender in the area of in the area of technology and that their insertion is taking place progressively by changing stereotypes.